2009
DOI: 10.1111/j.1365-2222.2008.03120.x
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a self‐administered Food Allergy Quality of Life Questionnaire for children

Abstract: The FAQLQ-CF is the first self-administered disease-specific HRQL questionnaire for food-allergic children. This questionnaire has a strong internal consistency and cross-sectional validity. It discriminates between children who differ in number of food allergies, and it was short and easy to use in the population studied. Therefore, the FAQLQ-CF may be a useful tool in clinical research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
185
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(199 citation statements)
references
References 32 publications
12
185
1
1
Order By: Relevance
“…The FAQLQ-CF contains 24 items and 4 domains, the FAQLQ-TF contains 23 items and 3 domains, and the FAQLQ-AF contains 29 items and 4 domains [13][14][15]. The total FAQLQ score is the sum of all the items divided by the number of items and ranges from 1 (minimal impairment in HRQL) to 7 (maximal impairment in HRQL) [18,19].…”
Section: Questionnairesmentioning
confidence: 99%
See 1 more Smart Citation
“…The FAQLQ-CF contains 24 items and 4 domains, the FAQLQ-TF contains 23 items and 3 domains, and the FAQLQ-AF contains 29 items and 4 domains [13][14][15]. The total FAQLQ score is the sum of all the items divided by the number of items and ranges from 1 (minimal impairment in HRQL) to 7 (maximal impairment in HRQL) [18,19].…”
Section: Questionnairesmentioning
confidence: 99%
“…Recently, as part of the EuroPrevall project, the first self-administered HRQL questionnaires specific for food allergy have been developed and validated: the Food Allergy Quality of Life Questionnaire-Child Form, -Teenager Form and -Adult Form (FAQLQ-CF, -TF, -AF). The FAQLQs showed good validity, internal consistency and discriminative abilities [13][14][15][16], but test-retest reliability was not extensively investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Although there is limited specific data on the camp environment, parallels may be drawn with families "dining out". For example, Avery and colleagues (2003) found that families frequently visit the same restaurant because they trust the establishment and know their food allergy will be catered for [26].…”
Section: Discussionmentioning
confidence: 99%
“…For those less than 8 years of age, the Food Allergy Quality of Life Questionnaire-Parental Form (FAQLQ-PF) is utilized and is standardized for patients 0 -12 years of age [25]. The Food Allergy Quality of Life Questionnaire-Child Form (FAQLQ-CF) questionnaire was the first food allergy-specific questionnaire developed for self-administration by children 8 to 12 years of age [26]. This tool addresses important issues around allergen avoidance, risk of accidental exposure, emotional impact, and dietary restrictions; however, it does not delve deeper into how children cope and adapt with their food allergies.…”
Section: Health-related Quality Of Lifementioning
confidence: 99%
“…It does appear that patients find PROMs acceptable in terms of time and effort: research by members of our team, administering HRQL questionnaires in an outpatient allergy clinic setting, identified very high response rates in children (73-94%) and adults (80-86%) and little questionnaire fatigue. [15][16][17] The intended use of PROMs by patients to inform effective choices in health care services requires further examination, 10,13 particularly in relation to informed decision-making and health literacy. 18 Asthma and related allergic disorders affect up to one in three of the UK population at some point in their lives, and are responsible for considerable morbidity and in some cases mortality.…”
Section: Introductionmentioning
confidence: 99%